Glosa o narcyzmie na marginesie Lodowych pól Zofii Nałkowskiej - Zawiszewska, Agata (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The article suggests a reading of Nałkowska’s first work, treated as a literary study of narcissism. In Lodowe pola Nałkowska made an unsuccessful attempt to express the work through an inner narcissistic conflict, giving the protagonist, Janka Dernowiczówna, the qualities of narcissistic personality, such as individualism, dandyism, estheticism, Nietzscheism, atrophy of instinct, need for self-control, stage directing of life, and never-satisfied self love. The author also transferred her own feeling of emotional neglect by her mother in infancy onto the feeling of rejection of Janka’s proposal by Rosławski. The image and experience of “ice fields” as the emptiness of life, chaos, and powerlessness, becomes a metaphor of narcissistic “abandonment depression”, which became, in Nałkowska’s later work, a constantly present emotional mood and a source of artistic “tanatic imagination”.